1991
DOI: 10.1007/bf01319413
|View full text |Cite
|
Sign up to set email alerts
|

Oogenesis in the articulate brachiopodTerebratulina retusa

Abstract: A detailed ultrastructural description of oogenesis is presented for the articulate brachiopod Terebratulina retusa (Linnaeus), based on collections made between October 1985 and October 1986 from the Firth of Lorn, west coast of Scotland. Oogenesis has been divided into six stages, defined according to ultrastructural changes, which are thought to be important steps in the process of vitellogenesis. Special attention has been given to the possible mechanisms involved in the acquisition and assimilation of nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Measurements of egg size in a sample of Terebratulina retusa (James et al 1991) show a narrow range of variation and this pattern has been frequently observed in other living taxa. Thus, all modern rhynchonelliform brachiopods have lecithotrophic larvae.…”
supporting
confidence: 55%
“…Measurements of egg size in a sample of Terebratulina retusa (James et al 1991) show a narrow range of variation and this pattern has been frequently observed in other living taxa. Thus, all modern rhynchonelliform brachiopods have lecithotrophic larvae.…”
supporting
confidence: 55%
“…Mixed vitellogenesis. In Terebratulina retusa there are special accessory cells located between the follicular cells and the oolemma (James et al, 1991b).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors (James et al, 1991b;Williams et al, 1997) suggest that the follicular envelope of brachiopod oocytes may regulate the flow of nutrients into the oocyte, but experimental evidence to support this assumption is needed.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Pigments are usually metabolic products transferred from food. The most common pigments for the colouration of marine organisms are carotenoids, which give a brownish to orange colour to both the soft tissue and the shell (James et al 1991). The colouration of the shell is thought to be the disposal of such waste by products of metabolism (Kelley & Swann 1988).…”
Section: Colour Pattern In K Kultavasaensismentioning
confidence: 99%